The haunting - Preston, Natasha (New York : Delacorte Press, 2023)
b
Ages 12 and up.
Keywords: Murder -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Horror fiction; Young adult fiction